Influência de diferentes métodos de preparo e sistema adesivo na resistência máxima de adesão à dentina bovina e humana - Novais, Veridiana Resende (2007)
The aim of this study was: determine the microtensile bond strength (μTBS) of two adhesives, one total-etch and one self-etching primer, to bovine dentin prepared with a carbide bur, a diamond rotary instrument and CVD bur; and evaluated the microtensile bond strength (μTBS) of two adhesives, one etch-and-rinse and one self-etching, to bovine and human dentin prepared with a carbide bur and diamond rotary instrument. For the first evaluation, forty-two bovine incisors with similar age were randomly divided into three groups according to surface preparation: carbide bur CB, diamond rotary instrument PD and CVD bur. For the second evaluation, twenty-eight bovine incisors and twenty-eight human molars were randomly divided into two groups according to surface preparation: carbide bur CB and diamond rotary instrument PD. Each group (n=7) was bonded using a total-etch adhesive (Scotch Bond Multi Purpose) - SBMP and one self-etching primer (Clearfil SE Bond) - CfSE. The cavities were incrementally restored with composite resin. The teeth were sectioned into 0.8 mm2 beam, and loaded to failure at a crosshead speed of 0.5 mm/min using mechanical machine. Microtensile bond strength data were analyzed using analysis of variance and Tukey test (p<0.05). The results of first evaluation showed that μTBS values of PD and CVD were similar and higher than CB. And μTBS values of CfSE were always higher than SBMP. For the second evaluation, the dates do not show statistically difference between substrate, adhesive and rotary instrument (p=0,495). But have difference between substrate and adhesive (p=0,000), and substrate and rotary instrument (p=0,000). A μTBS value of SBMP in human dentin was similar to CfSE, and in bovine dentin, the μTBS values was smaller invariable of rotary instrument used. And human teeth show higher μTBS values than bovine teeth. Hence, for bovine dentin, μTBS values of PD were significantly than CB, and show difference only to bovine dentin, not been influence for human dentin. The bovine dentin show μTBS values significantly higher when to CfSE, while in human dentin, both adhesive system show similar μTBS values. Ten, the type of rotary instrument and adhesive system influence the μTBS values differently between bovine and human substrate.